2010
DOI: 10.4103/1596-3519.68354
|View full text |Cite
|
Sign up to set email alerts
|

Premenstrual dysphoric disorder among medical students of a Nigerian university

Abstract: The rate of PMDD in this study is high. Dysmenorrhoea of moderate/severe intensity correlated significantly with the possibility of having PMDD. Efforts should therefore be made to alleviate the pain associated with menses. In addition, the College's health-care providers should take into account the issues of dysmenorrhoea and its management more seriously by intensifying health education on dysmenorrhoea and PMDD in order to improve the quality of life of the students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
34
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 12 publications
13
34
3
1
Order By: Relevance
“…Bailey and colleagues found that 40% of women diagnosed with PMS or PMDD also had comorbid affective or anxiety disorders. [29] Contrary to the study by Cohen and colleagues that found an association of PMDD and lower education, [30] other studies have found PMS/PMDD had higher prevalence rates among students, [15,29] which is also supported by the findings of Takeda and colleagues that showed that one half of female students experienced both irritability and depression. [31] Limited information about the cause and treatment of PMDD may also contribute to the high prevalence rate of PMDD in adolescent girls.…”
Section: Prevalence Of Pmddmentioning
confidence: 92%
See 2 more Smart Citations
“…Bailey and colleagues found that 40% of women diagnosed with PMS or PMDD also had comorbid affective or anxiety disorders. [29] Contrary to the study by Cohen and colleagues that found an association of PMDD and lower education, [30] other studies have found PMS/PMDD had higher prevalence rates among students, [15,29] which is also supported by the findings of Takeda and colleagues that showed that one half of female students experienced both irritability and depression. [31] Limited information about the cause and treatment of PMDD may also contribute to the high prevalence rate of PMDD in adolescent girls.…”
Section: Prevalence Of Pmddmentioning
confidence: 92%
“…The prevalence rate of 36.1% of PMDD was reported by Issa and colleagues in a study among medical students. [15] Niser and colleagues reported a PMDD prevalence rate of 5.8% among unmarried…”
Section: Prevalence Of Pmddmentioning
confidence: 99%
See 1 more Smart Citation
“…They correlated loss of productivity to the bad psychological wellbeing. Fifth, Baba Aissa et al (2010) [18] had studied premenstrual dysphoric disorder among medical students at a Nigerian university. They found that PMS of moderate/severe intensity was significantly correlated with poor psychological wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…В швейцарском общепопуляционном исследовании [21] выявлено, что 3% женщин репродуктивного возраста имеют критерии для диагностики ПМДР; индийские ис-следователи [22] сообщают о частоте в 6%; сплошное по-пуляционное исследование нигерийских студентов-меди-ков [23] показало, что у 36% респонденток имеются крите-рии для диагностики ПМДР.…”
Section: критерии пмдр в Dsm-5unclassified